2012
DOI: 10.1111/j.1095-8649.2012.03338.x
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the induction of cyp1A and related genes in cultured rainbow trout Oncorhynchus mykiss. Additional considerations for the use of EROD activity as a biomarker

Abstract: Two rainbow trout Oncorhynchus mykiss fish farms were repeatedly sampled in order to observe the variability of ethoxyresorufin-O-deethylase (EROD) activity and of related genes in the liver. Fish coming from fish farm A exhibited EROD levels that could be considered as basal according to the scientific literature, however, EROD activity in fish coming from fish farm B was significantly increased. This was accompanied by augmented aryl hydrocarbon receptor (ahr) and cytochrome P4501A (cyp1A) messenger RNA expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…In some previous studies, sex-related differences in P450 activity during the reproductive cycle have been reported in other fish (Andersson, 1990;Gray et al, 1991). Moreover, some previous studies showed a good correlation between EROD activity and CYP1A mRNA expression in fish (Quiró et al, 2007;Valdehita et al, 2012), but others also reported a poor correlation between EROD activity and CYP1A mRNA expression (Della Torre et al, 2010;Kammann et al, 2008;Karaca et al, 2014).…”
Section: Discussionmentioning
confidence: 92%
“…In some previous studies, sex-related differences in P450 activity during the reproductive cycle have been reported in other fish (Andersson, 1990;Gray et al, 1991). Moreover, some previous studies showed a good correlation between EROD activity and CYP1A mRNA expression in fish (Quiró et al, 2007;Valdehita et al, 2012), but others also reported a poor correlation between EROD activity and CYP1A mRNA expression (Della Torre et al, 2010;Kammann et al, 2008;Karaca et al, 2014).…”
Section: Discussionmentioning
confidence: 92%
“…The procedure for the determination of EROD activity was selected according to multiple scientific literature supporting the effectiveness of the protocol (Lammel et al, 2015;Quesada-García et al, 2013, 2015Valdehita et al, 2012) and its reproducibility was standardized and validated in preliminary assays with different PAHs and flavonoids such as benzo[a]pyrene, pyrene and beta-naphthoflavone. EROD activity in liver of A. metae was determined in a S9 fraction according to the method described by Valdehita et al (2012) after standardization. Approximately 30 mg of liver was gently homogenized at 4 C in 1 mL of homogenization buffer (0-1 M Tris-HCl pH 7,0-25 mM sucrose, 150 mM KCl, 1 mM EDTA, 1 mM DTT, 0-25 mM PMSF and 20% glycerol).…”
Section: Erod Activity Assaymentioning
confidence: 99%